Incorrect Nominations of Persons as Violations of Journalistic Ethics in Modern Materials of Sensitive Media Content (On the Mateials of Ukrainian Media) - Shulska, Nataliia; Kostusiak, Nataliia; Pykaliuk, Roman; Sypchenko, Inna; Bondarenko, Olena; Dubetska, Oksana; Yevdokymenko, Iryna; Zyma, Olha (My University, 2023)
The article presents a study of the socially sensitive content of the Ukrainian informal space, in particular, regarding the nomination of persons based on various characteristics. The incorrect names used for nominating persons of various social groups (those with disabilities, certain diseases, according to age characteristics, ethnicity, social status, those who suffered as a result of the Russian-Ukrainian war, etc.) were identified, structured, and comprehensively analyzed. Relevant counterparts correlating with the rules of social etiquette are proposed for each incorrect nomination. The materials of the study were media texts, which present linguistic units - the nominations of people – that do not correspond to the journalism of tolerance, and in some places also give rise to the language of enmity. It is noted that anormative nominations are presented both in the title complex of publications and in the text content itself. It was observed that the use of incorrect nominations of persons (“disabled”, “blind”, “deaf”, “wheelchair”, “handicapped”, “special child”, “schizophrenic”, “person with oncology”, “blonde driving”, “negro”, “Asian”, “homeless”, “gypsy”, etc.) not only carries negative semantics, but is offensive to these categories of people, violates language and ethical norms, indicates a lack of gender sensitivity, and shows the unprofessionalism of journalists and editors. It was found that the media often do not avoid stereotypes regarding the correct portrayal of those with disabilities, and deliberately, for the sake of sensationalism and attracting attention, detail the disabilities of such persons, pitying them out of measure, and sometimes even over-heroizing them. The headlines testifying to the use of incorrect words or phrases of a discriminatory nature to denote a person's ethnic, national, or racial affiliation have been recorded. False lexemes based on people's age characteristics were also detected in stories about those who live alone, who are homeless, have drug or alcohol addiction. Often, for the sake of sensationalism and clickbait, journalists attach rating labels to people even before a court decision, resort to hyperbolized and provocative media titles, and “taste” violence, death, or crime. Incorrect nominations, which became especially widespread in the conditions of the Russian-Ukrainian war, to denote people who changed their place of residence in connection with active hostilities, were also analyzed.
Keywords: incorrect nominations of persons; media; journalistic ethics; sensitive content; Ukrainian language; professional communication